Endowments, Specialization, and Policy - Cadot, Olivier; Shakurova, Yuliya (2012)
The paper explores the relationship between industry shares in production and their determinants including factor endowments, technology, and government policies, in a GDP-function framework. We use a new international panel dataset on production and trade compiled by the World Bank. As an intermediate step we calculate Hicks-neutral productivity indices that vary across industries, time, and countries. We find that own-TFP is robustly associated with industry shares across time and countries and that, after correcting for these productivity differences, output shares are related to factor endowments (Rybczynski effects) in a plausible way. Once Rybczynski effects are controlled for, we find little evidence of demand-side policies (import tariffs) affecting the allocation of resources; we find, however, more role for supply-side policies as the relative size of capital-intensive industries is positively associated with infrastructure--capital endowments.